ChemInform Abstract: Facile Synthesis of 2‐Fluoro‐1, 3‐dicarbonyl Compounds with Aqueous Hydrofluoric Acid Mediated by Iodosylarenes. Issue 14 (8th April 2014) - Kitamura, Tsugio; Kuriki, Satoshi; Muta, Kensuke; Morshed, Mohammad Hasan; Muta, Kazutaka; Gondo, Keisuke; Hori, Yuji; Miyazaki, Masaya
Abstract Fluorination of 2‐substituted ethyl 2‐oxocyclohexanecarboxylate and diethylmalonate fail.